The Effect of Zumba on Dysmenorrhea in Students of the Faculty of Medicine, Diponegoro University - Humairoh Mutha'alimah; Marijo Marijo; Yuli Trisetiyono; Putri Sekar Wiyati (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Dysmenorrhea is the most common symptom of most menstrual complaints, and has a greater risk of causing disease than any other gynecological complaints. Dysmenorrhea can be accompanied by other symptoms such as sweating, tachycardia, nausea, vomiting, headache, diarrhea and tremors. Dysmenorrhea causes activity limitations which can affect productivity and quality of life of a woman.Objectives: Determine the effects of Zumba on primary dysmenorrhea among female students of the  Faculty of Medicine, Diponegoro University.Method: This study used an analytic observational study with a pretest-middletest-posttest design. A participants of 49 students were divided into 2 groups. The control group (K) was not given the Zumba intervention. Treatment group (P) was given 8-week intervention program with two 60’ sessions per week of Zumba. Data were collected before, during, and after Zumba intervention using a self-administrated dysmenorrhea questionnaire and VAS pain scale.Result: Based on the VAS pain scale and dysmenorrhea questionnaire, the mean value of the control group and treatment group was K: 2,02; 1,92; 2,06; P: 1,98; 1,98; 2,04. Statistical analysis using Friedman tests showed statistically not significant differences (p > 0,05).Conclusion: Zumba exercise did not have a significant difference in reducing dysmenorrhea pain levels.Keyword: Zumba exercise, exercise, primary dysmenorrhea, menstrual pain